This case theory law school: the conundrum of teaching or having impact? / Wan liza Md Amin, Ainul Hafiza Zainudin and Puteri Sofia Amirnuddin - Md Amin, Wan liza; Zainudin, Ainul Hafiza; Amirnuddin, Puteri Sofia (2018)
"This Case Theory" is a study conducted to address the current conundrum faced by the law School in Malaysia. The dilemma lies with the new role and expectation of Modern Universities in the 21st century. It is whether we are "Doing" or Having Impact?" The debate of whether law school are merely doing a law program? or have the law school succeeded to equipped potential law graduates with all the right practical skills have been a continuous and ongoing for decades. Are law school doing it right? Yes, No and Why? It is a Yes because law school's module has undergone several reappraisal stages and "re-branding" of their teaching methods and its modules to stay relevant to the legal industry in Malaysia. The desire to "keep up" thus far is evidenced by three main methods adopted by law school. Simulations, Role play, and attachment program during semester break are common methods adopted by all the law school in Malaysia. This paper proposes three (3) effective teaching methods on final year's subjects combining technological apps complimenting the present teaching method for theory using traditional pedagogy. The case theory also processes the content of the simulation are the key factor in making an impact in the legal industry. Thus we have designed our traditional pedagogy and adopted recent development in teaching pedagogy through augmented reality concept. The conclusion of the paper proposed that Conceptual Traditional teaching need to be translated to the legal industry needs via real simulation the best impacts to legal education translates all the legal theories to practicum skills to address the legal market needs.